1999
DOI: 10.1159/000016574
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Factors Affecting Dental Erosion in Children

Abstract: Dental erosion is becoming a major dental problem in both children and adults. The aim of this study was to measure the salivary flow rates, buffering capacity and mutans streptococci counts in children with erosion, and compare them to age– and sex–matched caries–free and caries–active individuals to establish which factors may be important in erosion. The study was conducted as a case–control study with standard methods of salivary and mutans streptococci measurement. The results showed significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1
18

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 12 publications
(15 reference statements)
6
48
1
18
Order By: Relevance
“…17 Salivary buffer capacity seems to be a determinant factor on dental erosion, which is becoming a major dental problem in both children and adults. 18 Low CAVI concentrations in the saliva were associated with the prevalence of dental caries, especially in individuals with poor oral hygiene. 19 Experimental evidences indicate that CAVI in saliva penetrates plaque and facilitates acid neutralization by salivary bicarbonate.…”
Section: Introductionmentioning
confidence: 99%
“…17 Salivary buffer capacity seems to be a determinant factor on dental erosion, which is becoming a major dental problem in both children and adults. 18 Low CAVI concentrations in the saliva were associated with the prevalence of dental caries, especially in individuals with poor oral hygiene. 19 Experimental evidences indicate that CAVI in saliva penetrates plaque and facilitates acid neutralization by salivary bicarbonate.…”
Section: Introductionmentioning
confidence: 99%
“…Quando se estuda a erosão dentária, é importante verificar as propriedades das bebidas ingeridas, como também sua interação com o organismo (9,25,26) . O valor de pH de 5,5, no qual os cristais de hidroxiapatita começam a se dissolver, é conceituado como pH crítico para a desmineralização dentária, de modo que, abaixo desse valor, o esmalte está em risco de sofrer descalcificação (9) .…”
Section: Resultsunclassified
“…O valor de pH de 5,5, no qual os cristais de hidroxiapatita começam a se dissolver, é conceituado como pH crítico para a desmineralização dentária, de modo que, abaixo desse valor, o esmalte está em risco de sofrer descalcificação (9) . Portanto, em tese, uma bebida com pH abaixo desse valor será capaz de causar erosão no esmalte dentário, mesmo que grande parte da solução seja deglutida e pouco fique misturado com a saliva (25) . Tipicamente, isotônicos são bebidas não carbonatadas, de elevada acidez (27) .…”
Section: Resultsunclassified
“…It was concluded that children with dental erosion consumed more carbonated beverages than their controls. The swishing and holding habit found in 43% of the subjects was also noted as an aggravating factor for dental erosion [22]. On the other hand, Smith and Shaw considered the mode of intake of acidic beverages to be of less importance than the frequency since the pH of the tooth surface requires at least five minutes in order returning to its resting level after dropping [23].…”
Section: Behavioral Factors Drinking Habits and Pattern Of Consumptionmentioning
confidence: 99%